2022
DOI: 10.3390/ijerph19042361
|View full text |Cite
|
Sign up to set email alerts
|

What Should Be Considered When Evaluating the Quality of Home Care? A Survey of Expert Opinions on the Evaluation of the Quality of Home Care in Japan

Abstract: Intending to obtain scientific evidence to use in developing indicators for evaluating the quality of home care, we surveyed doctors, nurses, and other home care professionals to determine the points they consider to be essential in evaluating home care. We investigated all 901 clinics registered to the National Association of Medical Institutions Supporting Home Care and a random sample of 600 Visiting Nurse Service stations registered to the National Association for Visiting Nurse Service in Japan. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Although home care for disabled older adults can decrease hospital care costs, resources vary widely between individuals and families. Studies have found that most older people do not receive adequate care services at home, especially those with particular diseases ( 13 15 ). For example, approximately one quarter of older persons with memory problems reported that they did not receive adequate care services, and that even a combination of informal and formal home care was insufficient to meet their needs ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although home care for disabled older adults can decrease hospital care costs, resources vary widely between individuals and families. Studies have found that most older people do not receive adequate care services at home, especially those with particular diseases ( 13 15 ). For example, approximately one quarter of older persons with memory problems reported that they did not receive adequate care services, and that even a combination of informal and formal home care was insufficient to meet their needs ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…This form of care is actively practiced in some countries, including Japan, where reimbursement for home care is available, including for patients with cancer and palliative care needs. 3 , 4 In Japan, a state of emergency due to COVID‐19 was declared in April 2020, and to date, the infection has not been well controlled. Hospitals have implemented restrictions on the number of people who can visit hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
“…Home care is a form of care in which patients stay at home with the help of their families, nurses, care workers, doctors and other health care professionals. This form of care is actively practiced in some countries, including Japan, where reimbursement for home care is available, including for patients with cancer and palliative care needs 3,4 . In Japan, a state of emergency due to COVID‐19 was declared in April 2020, and to date, the infection has not been well controlled.…”
Section: Introductionmentioning
confidence: 99%